Evaluation of Corn Protein Source on Feed Intake Preference in Nursery Pigs - Ethan B. Stas; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 180 pigs (241 × 600, DNA; initially 17.0 ±1.6 lb) were used to determine feed intake preference from various corn protein sources. A series of 5-day preference trials were used with two diets offered within each comparison with feeder location rotated daily within each pen. Feed consumption was used to determine preference between each diet comparison. There were 6 replicates of each diet comparison. The corn protein sources utilized in this experiment included: fermented corn protein, high protein distillers dried grains with solubles (HPDDGs), whole stillage solids (approximately 2/3 content of fermented corn protein), and thin stillage solids (approximately 1/3 content of fermented corn protein). Fermented corn protein and HPDDGs were included in the diet at 15% as a replacement for corn. Whole stillage solids and thin stillage solids were included in the diet at 10% and 5%, respectively, as a replacement to corn to match its contribution in fermented corn protein. The control diet was a standard nursery diet. Diet comparisons included: 1) Control vs. Fermented corn protein; 2) Whole stillage solids vs. Fermented corn protein; 3) Thin stillage solids vs. Fermented corn protein; 4) HPDDGs vs. Fermented corn protein; 5) Control vs. Whole stillage solids; 6) Control vs. Thin stillage solids. For comparison 1, pigs preferred (P<0.001) the control diet by consuming 82.5% of their intake with this diet compared with the diet containing fermented corn protein. For comparison 2, there was no difference (P>0.05) in feed consumption of diets containing whole stillage solids and the fermented corn protein. For comparison 3, pigs preferred (P= 0.001) the diet containing thin stillage solids by consuming 75.8% of their intake with this diet compared to the diet containing fermented corn protein. There was no difference when comparing fermented corn protein and whole stillage solids, but thin stillage solids had a higher percentage intake than fermented corn protein. Therefore, it is likely that whole stillage solids are the component of fermented corn protein that negatively affect feed consumption.
Keywords: corn protein; feed intake; preference; nursery pig